Simulation of high velocity inlet cyclone separator using Computational Fluid Dynamic (CFD) approach: article - Ab Rahim, Nur Azira; Zainal Abidin, Hanafiah (2017)
This paper presents a computational fluid dynamics (CFD) calculation to evaluate the effect of velocity of inlet cyclone on the pressure drop of cyclone separator.The simulation of CFD code Fluent 6.1 is used to iterate the result. The CFD simulations predict excellently the cyclone pressure drop under different inlet velocity. The result shows that the pressure is increase with the increase of velocity.